Aspirasi Afektif dan Hasrat yang Dimediasi: Peran Media Sosial dan Drama Korea dalam Membentuk Idealisme Romantis Kalangan Mahasiswa di Ambon - Hukunala, Melkianus; Angkotasan, Sulaiman; Mahulauw, Syaifulrijal (Universitas Pattimura, 2022)
This study investigates how digital media—particularly TikTok and Korean dramas (K-Dramas)—shape affective aspirations and romantic desires among university students at Pattimura University in Ambon. The focus lies in exploring how young adults imagine and idealize romantic partners through media representations they routinely consume, and how these representations are mediated by local cultural contexts. Employing a qualitative interpretative approach, the research draws on in-depth interviews, focus group discussions, and light netnographic observation of media interactions in Ambon. Data analysis uses thematic analysis to examine meaning-making processes, affective dynamics, and gender representations within popular culture. Findings reveal that romantic portrayals in K-Dramas and TikTok function not merely as entertainment, but as symbolic frameworks shaping relational aspirations and emotional values among youth. The study highlights ongoing negotiations between global romantic ideals and local identities in the postcolonial social setting of Eastern Indonesia. Its novelty lies in integrating theories of affective sociology and mediatization within an underexplored peripheral context, while introducing “affective aspirations” and “mediated desires” as conceptual tools for analyzing contemporary intimacy. This research contributes to cultural and affective sociology by demonstrating that love and intimacy are not purely personal experiences, but socially constructed through the symbolic economy of digital media and global cultural flows.